Economic Freedom and Private Capital Inflows in Selected South Asian Economies: A Dynamic Panel Data Evidence. (June 2018) - Ullah, Assad; Anees, Muhammad; Ali, Zahid; Khan, Muhammad Ayub
Greater inflows of private capital are regarded to be very beneficial for the economic development. This study explores the relationship between economic freedom and private capital inflows in selected South Asian economies. The study comprises of six South Asian countries (India, Pakistan, Bangladesh, Sri Lanka, Nepal and Maldives). Data from 2002 to 2011 have been utilized, and the model is estimated by employing the system generalized method of moments (GMM) approach. Empirical results reveal a significant positive relationship between economic freedom and private capital inflows. The study transpired that economic freedom is potent determinant of private capital inflows. The results further established that growth in market size and official development assistance has significant positive association with private capital inflows, whereas exchange rate exhibits significant negative relationship with the inflows of private capital, thereby confirming the existing literature. Moreover, the relationship among inflation, natural resources and private capital inflows came out to be inconclusive. To lure more inflows of private capital towards the region, management authorities need to ensure high degree of economic freedom. Creation of investment-friendly climate, corruption-free environment, tax breaks in selective sectors, removing trade barriers, equity market liberalization and consistency in the government policies is advisable in this regard.